PENERAPAN WATERFRONT DEVELOPMENT PADA PERENCANAAN FLOATING MARINA DI KOTA KENDARI - Hidayat, Rahmad; Said, Burhan; Syukur, La Ode Abdul (Universitas Halu Oleo, 2021)
ABSTRAKKota Kendari memiliki potensi pengembangan pariwisata bahari yang sangat besar. Pengembangan marina merupakansalah satu cara pemenuhan aspek amenities dan accessibility pada wisata bahari. Floating Architecture merupakan solusisustainable bagi pengembangan pesisir dan menjadi jalan tengah antara pembangunan & konservasi. Floating Architecturemerupakan bagian dari konsep Waterfront Development. Perancangan ini bertujuan untuk memperoleh suatu rancanganmarina di Kota Kendari yang menerapkan konsep Floating Architecture dan Waterfront Development di dalamnya. Dalamperancangan ini metodologi yang digunakan adalah metode Analisis Sintesa. Hasil perancangan memperoleh polapengembangan marina sebagai fasilitas bagi kapal wisata (yacht) dan perahu kecil dengan fasilitas akomodasi dan rekreasi.Selanjutnya penerapan Floating Architecture difokuskan pada aspek struktural bangunan dengan penggunaan sub structureberupa sistem concrete tray. Sementara penerapan Waterfront Development dilakukan dengan pengolahan tapak yang fokuspada aspek waterfront planning, pubic acces, cultural relics & heritage, environment & ecosystem, serta aspek tourism andrecreation.Kata Kunci: Kota Kendari, Marina, Floating Architecture, Waterfront DevelopmentABSTRACTKendari City has a huge potential for marine tourism development. Marina establishment is one way to fulfill theaspects of amenities and accessibility in marine tourism. Floating Architecture is a sustainable solution for coastaldevelopment and a middle ground between development & conservation. Floating Architecture is part of WaterfrontDevelopment concept. This project aims to obtain a marina design in Kendari City that applies the concept of FloatingArchitecture and Waterfront Development in it. In this project the methodology used is the Analysis Synthesis method. Theresults of the design obtained a pattern of marina development as a facility for yacht and small boats with accommodationand recreation facilities. Furthermore, the application of Floating Architecture is focused on the structural aspects of thebuilding by using a sub structure in the form of a concrete tray system. While the implementation of WaterfrontDevelopment is carried out by site processing that focuses on aspects of waterfront planning, public access, cultural relics& heritage, environment & ecosystem, as well as aspects of tourism and recreation.Keywords: Kendari City, Marina, Floating Architecture, Waterfront Development